STRATEGI PEMASARAN SUSU SAPI PERAH DI KUD MUSUK KABUPATEN BOYOLALI - Annida Fidiena; Kusriani Prasetyowati; Suswadi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2020)
Milk as one of the livestock products is a source of animal protein which is increasingly needed in improving the quality of life of the community. The objectives of this study are to find out internal and external factors, alternative strategies and strategic priorities that can be applied to the marketing of dairy cows in KUD Musuk, Boyolali Regency. This study uses descriptive basic methods. Determination of the location of the research was carried out purposively in the KUD Musuk Boyolali Regency. Data sources used are primary data and secondary data. Data collection techniques were carried out with interviews, questionnaires, documentation and literature studies. The analysis technique used is; (1) SWOT analysis to identify internal factors and external factors (2) SWOT matrix to formulate alternative strategies; and (3) QSPM matrix to determine the prioritization of product marketing strategies. The results of the study stated that there were 3 alternative strategies namely increasing milk production for dairy cows and developing cooperation with IPS, maintaining continuity of production and, increasing the number of employees and encouraging farmers and employees to attend training. From the alternative strategies above, we can prioritize strategies that can be applied to marketing milk cows milk in KUD Musuk, Boyolali Regency based on the QSPM matrix, which is to maintain continuity of production.